Pertumbuhan dan Produksi Sorgum bicolor pada Kultur Fungi Mikoriza Arbuskula (FMA) dengan Sistem Fertigasi dan Fortifikasi Nutrisi Berbeda: Growth and Production of Sorghum bicolor in Arbuscular Mycorrhizal Fungi (AMF) Cultures with Different Fertigation and Nutrient Fortification Systems (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
Arbuscular mycorrhizal Fungi (AMF) is a microorganism that biologically affects plant enzymes and plant nutrients. AMF production development techniques need to be improved with the addition of nutritional fortification to produce quality AMF products. The research aimed was to cultivate AMF with complete fertilizer nutrition and different fertigation systems on Sorghum bicolor. The study used a 2 x 3 factorial randomized design with A factor: fertigation system (flat and terraced) and B factor: fertilizer nutrient levels (1000ppm, 2000ppm, 3000ppm). The results showed that the flat fertigation system had a significant different (p